2018
DOI: 10.1007/s11033-018-4488-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in angiogenesis

Abstract: Angiogenesis extends pre-existing blood vessels to improve oxygen and nutrient delivery to inflamed or otherwise hypoxic tissues. Mitochondria are integral in this process, controlling cellular metabolism to regulate the proliferation, migration, and survival of endothelial cells which comprise the inner lining of blood vessels. Mitochondrial Complex III senses hypoxic conditions and generates mitochondrial reactive oxygen species (mROS) which stabilize hypoxia-inducible factor (HIF-1α) protein. HIF-1α induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 78 publications
0
48
0
1
Order By: Relevance
“…Mitochondria function as an O 2 sensor and transmit a hypoxic signal by releasing ROS to the cytosol [ 94 ]. Hypoxia stimulates mitoROS production such as H 2 O 2 from mitochondrial complex III and the ROS trigger HIF1-α stabilization [ 94 , 95 , 96 ], which in turn increases the transcription of angiogenic genes such as VEGF [ 97 ]. Thus, mitochondria regulate angiogenic responses by controlling cellular metabolism linked to mitoROS.…”
Section: Role Of Mitochondria-derived Ros In Angiogenesismentioning
confidence: 99%
“…Mitochondria function as an O 2 sensor and transmit a hypoxic signal by releasing ROS to the cytosol [ 94 ]. Hypoxia stimulates mitoROS production such as H 2 O 2 from mitochondrial complex III and the ROS trigger HIF1-α stabilization [ 94 , 95 , 96 ], which in turn increases the transcription of angiogenic genes such as VEGF [ 97 ]. Thus, mitochondria regulate angiogenic responses by controlling cellular metabolism linked to mitoROS.…”
Section: Role Of Mitochondria-derived Ros In Angiogenesismentioning
confidence: 99%
“…Mitochondrial complex III can sense hypoxic conditions and produce ROS, which stabilizes the HIF-1α protein. It has been reported that binding of terpestacin to the ubiquinol-cytochrome c reductase binding protein (UQCRB) subunit of complex III restrains HIF-1α stabilization by inhibiting ROS production, causing suppression of angiogenesis, which coincides with decreased VEGF levels 97 . Thus, the ETC components including complex I, complex II (SDH), and complex III play an important role in HIF stabilization 2 , 98 .…”
Section: Interplay Between Mitochondrial Dysfunctions and Hifsmentioning
confidence: 99%
“…In addition to being the powerhouse of the cell, mitochondria also play critical roles in reactive oxygen species (ROS) generation, Ca 2+ homeostasis, and cell death [6][7][8]. ROS derived from mitochondria could stabilize hypoxia-inducible factor 1α (HIF-1α), and HIF-1α, in turn, promotes VEGF expression, contributing to angiogenesis [9]. Mitochondrial dysfunction is associated with the development of many diseases, including cardiovascular diseases [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%